The noticer : sometimes, all a person needs is a little perspective - Andrews, Andy, 1959- (Nashville, Tenn. : Thomas Nelson, 2009)
In this blend of fiction, allegory, and inspiration, Andrews tells the story of Jones--a mysterious man who shows up when things look the darkest for the people of Orange Beach, Alabama, and whose unique gift of noticing things that others miss helps us understand why things happen and what we can do about it.
Includes bibliographical references.
Keywords: Conduct of life; Conduct of life; Perspective (Philosophy); Insight; Conduct of life; Insight; Perspective (Philosophy); Conduct of life; Perspective (Philosophy); Thought and thinking